1995
DOI: 10.1007/bf03192289
|View full text |Cite
|
Sign up to set email alerts
|

Danggui (Angelica sinensis) affects the pharmacodynamics but not the pharmacokinetics of warfarin in rabbits

Abstract: Danggui is a popular traditional Chinese medicinal (TCM) herb which is easily obtained by the public. The effects of Danggui on the pharmacokinetics and pharmacodynamics of warfarin were studied in rabbits. Single subcutaneous doses (2 mg/kg) of warfarin were administered to 6 rabbits with or without 3 days treatment with oral Danggui extracts (2 g/kg twice daily). Plasma warfarin concentrations were measured by high performance liquid chromatography (HPLC) for 72 h after each of the two warfarin doses. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 7 publications
3
21
0
Order By: Relevance
“…We reported the clinical observations on interactions between some popular CM herbs and warfarin with experimental animal studies. Danshen (Salvia miltiorrhiza) had effects on both the pharmacodynamics and pharmacokineties of warfarin in rats (Lo et al, 1992), whereas danggui (Angelica sinensis) affected the pharmacodynamics but not the pharmacokinetics of warfarin in rabbits (Lo et al, 1995).…”
Section: The Likelihood For Interaction Of Drug-cm Products Interactionsmentioning
confidence: 99%
“…We reported the clinical observations on interactions between some popular CM herbs and warfarin with experimental animal studies. Danshen (Salvia miltiorrhiza) had effects on both the pharmacodynamics and pharmacokineties of warfarin in rats (Lo et al, 1992), whereas danggui (Angelica sinensis) affected the pharmacodynamics but not the pharmacokinetics of warfarin in rabbits (Lo et al, 1995).…”
Section: The Likelihood For Interaction Of Drug-cm Products Interactionsmentioning
confidence: 99%
“…One case report of male gynecomastia was purportedly caused by dong quai ingestion. 26 No significant adverse effects are reported in the literature; however, a case report 27 and results of animal research 28 suggest a possible herb-drug interaction between donq quai and warfarin. There are numerous dong quai products in the American marketplace, the majority of which are combination preparations.…”
Section: Safetymentioning
confidence: 99%
“…A randomised, open-label, controlled study of newly diagnosed ischaemic stroke patients (n = 35) found that two weeks of concomitant use of Panax ginseng extract 1.5 g with warfarin did not significantly affect peak values, INR and PT area under the curve, thus concluding that Panax ginseng did not influence the pharmacological action of warfarin. (27) (9,10) In vitro study (34,36) Animal study (35) Clinical study (11) -CYP1A1, 2C6, 2C11 inhibitor (35) -Displaces warfarin from HSA-warfarin (36) -Antiplatelet effect (34) -Coumarin-containing (33) Clinical study (37) Animal study (38) -CYP3A4 inducer (37) -CYP1A, 2C, 3A inducer (38) Ginkgo Ginkgo biloba Leaf: 银杏; Fruit: 白果 Case report (12,13) In vitro study (41,42) Clinical study (39) -Antiplatelet effect (39) -CYP1A2, 2C9, 2C19, 2E1, 3A4 inhibitor (41,42) Animal study (43) -CYP1A1, CYP1A2, CYP2B, CYP2C, CYP3A inducer (43) Clinical study (14,15,40) In vitro study (44) Dong quai Angelica sinensis Root: 当归 Case report (16) Animal study (45) -Coumarin-containing (33) ---…”
Section: Asian Ginseng 人参 (Panax Ginseng)mentioning
confidence: 99%
“…(33) Animal steady state studies have found that Dong quai significantly increased PT (45) without any effect on warfarin concentration, suggesting the presence of pharmacodynamics, but not pharmacokinetic interactions.…”
Section: Mechanism Of Interaction: Dong Quai On Warfarinmentioning
confidence: 99%